Reconstructing Kahoot for Mahārah Istimā’ Evaluation in Arabic Language Learning: A Critical Review - Ainun Nikmah; Aufa Rahma; Muhammad Jafar Shodiq (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The use of Kahoot in Arabic language learning is increasingly widespread, particularly in the Maharah Istimā’ evaluation activities. However, its implementation has not fully reflected the complexity of listening skill assessment because it remains largely oriented toward speed and accuracy in answering questions. This study aims to reconstruct the use of Kahoot so that it aligns with the authentic, contextual, and meaning-oriented principles of Maharah Istimā’s evaluation. This research employed a qualitative approach with a library research design through conceptual analysis of language evaluation theories and the characteristics of Kahoot as a digital learning medium. The literature was collected from scholarly indices in Google Scholar, ERIC, and Scopus-related databases published between 2019-2026. The findings indicate that the use of Kahoot in listening evaluation tends to reduce the listening process into answer-selection activities characterized by surface-level and non-contextual questions, thereby limiting the assessment of discourse comprehension and meaning interpretation. The study also found a mismatch between Kahoot-based evaluation practices and the principles of Arabic language evaluation, particularly in terms of authenticity, contextuality, and cognitive depth. Therefore, this study proposes a reconstruction through a shift toward meaning-oriented assessment, the application of contextual and cognitively engaging evaluation principles, and the repositioning of Kahoot as a pedagogical support tool rather than the primary orientation of evaluation. This study offers a conceptual framework for aligning gamified assessment tools with authentic listening evaluation principles in Arabic language pedagogy. The findings are expected to contribute to the development of more pedagogical and meaningful digital-based listening evaluation practices.